Effect of inside Surface Baffle Conditions on Just Drawdown Impeller Rotational Speed - Furukawa, Haruki; Ota, Tomoki; Kato, Yoshihito (International Journal of Chemical Engineering, 2024)
The effect of inside surface baffle installation conditions on the minimum impeller rotational speed for just the drawdown of floating solid NJD was investigated. The inside surface baffle condition is the condition in which a partial baffle is placed with a clearance between the baffle and the vessel wall. In this study, a baffle with an insertion length of 0.2 times the liquid height was used. Moreover, the effect of baffle angle on NJD was investigated. The NJD was measured visually at least three times. The results showed that the effect of the radial installation position of the inside surface baffle on NJD depended on the impeller position. In addition, even baffles placed parallel to the tangential flow were found to decrease NJD.